2018
DOI: 10.1016/j.amsu.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Epibulbar complex and osseous choristoma: Clinicopathological study with interesting associations

Abstract: Materials and methodsA retrospective cohort study of cases with tissue diagnosis of epibulbar choristoma in 2 centers presenting during the period: 2000–2016 with focus on cases of complex and osseous choristoma. Demographic and clinical data were collected by the resident from medical records. The histopathological slides were reviewed by 2 pathologists and cases of complex and osseous choristoma were analyzed by biostatical staff.Results120 epibulbar choristomas were identified. 13/120 patients (10.8%) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The prevalence of osseous choristoma in our hospital was 0.676%. Similar results were observed in a study conducted by Aldossary MM et al [ 2 ], in which among the 120 patients with myoblastoma of the ophthalmic surface, two had osteogenic myoblastoma, with a prevalence of 1.7%. Among the osseous choristoma cases in this study, one case was observed in a young woman, and it presented as a hard mass on the upper left temporal quadrant, which was in accordance with the previous reviews.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The prevalence of osseous choristoma in our hospital was 0.676%. Similar results were observed in a study conducted by Aldossary MM et al [ 2 ], in which among the 120 patients with myoblastoma of the ophthalmic surface, two had osteogenic myoblastoma, with a prevalence of 1.7%. Among the osseous choristoma cases in this study, one case was observed in a young woman, and it presented as a hard mass on the upper left temporal quadrant, which was in accordance with the previous reviews.…”
Section: Discussionsupporting
confidence: 90%
“…At present, there is no unified conclusion on the relationship between the occurrence and development of osseous choristoma and sex. Although it has been reported that young women tend to have a high incidence[ 4 - 7 ], the association with sex was not significant due to the small number of cases[ 2 ]. Additionally, osseous choristoma is observed more frequently in the right eye than in the left eye, and its sites are mainly distributed in the conjunctiva, sclera, and ophthalmic muscle, with most of them located in the fascia of the superior temporal quadrant[ 8 - 10 ], However, osseous choristoma occurring in the rectus muscle or eyelid is rare[ 6 ], and the frequency of these cases has not yet been statistically analyzed[ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex choristomas contain cells from two or more different tissue types, such as bone, cartilage, nerve, muscle, sebaceous secretions, or lacrimal tissues. Complex choristomas can be sporadic cases or can be associated with Goldenhar syndrome and LNSS (25)(26)(27)(28). For patient 24, the first biopsy of the nasal part showed a dermolipoma, and the result of the second biopsy of the temporal part disclosed a complex choristoma with immature hair follicle tissue, sebaceous gland, and hyperplasia of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%